The pleiotropic association between IL-10 levels and CVD prognosis: Evidence from a meta-analysis. (July 2019) - Ni, Shi-Hao; Sun, Shu-ning; Huang, Zeng-Yan; Huang, Yu-Sheng; Li, Huan; Wang, Jia-Jia; Xian, Shao-Xiang; Yang, Zhong-Qi; Wang, Ling-Jun; Lu, Lu
Highlights: Our analysis suggests IL-10 cannot be used as an independent risk indicator of MI. The risk associated with IL-10 levels in CVDs may be related to levels of IL-6. IL-10 may be considered a prognosis indicator in chronic heart failure. Abstract: We examined the precise association between IL-10 levels and cardiovascular disease (CVD) prognosis and explored the pleiotropic role of IL-10 in different cardiac pathologies. We performed a meta-analysis of cross-sectional and longitudinal studies investigating IL-10 levels. Meta-regression analyses were used to determine the cause of the discrepancies. To assess publication bias, funnel plots were constructed, and Egger's tests were performed. Data from the GSE58015 dataset were used to investigate the levels of IL-10 under certain conditions. Because of substantial heterogeneity in the data used to compare the IL-10 levels between patients with CVD and healthy people, we could not determine the differences between the healthy controls and patients with ischemic or nonischemic pathologies (p > 0.05). The analysis of the association between IL-10 levels and CVD prognosis indicated that higher IL-10 levels were significantly associated with a poor prognosis in patients with nonischemic pathologies (HR = 1.10, 95% CI = 1.00–1.20, p = 0.043) but differentially associated with the prognosis of patients with ischemic pathologies based on the sampling time point (before percutaneous coronary intervention (PCI): HR = 4.90, 95% CI = 1.24–19.30, p < 0.001; after PCI: HR = 0.57, 95% CI = 0.43–0.75, p = 0.023). The meta -regression analysis showed that the pooled HR of the IL-10 levels was positively correlated with the IL-10/IL-6 ratio (β = 0.644, p = 0.024). The funnel plots and Egger's tests revealed no statistically significant bias in our meta-analysis (p > 0.1). Furthermore, our data mining analysis supported our findings. Our analysis showed that IL-10 levels may be pleiotropically associated with the CVD prognosis possibly based on the type of pathology, disease stage and levels of other proinflammatory factors, such as IL-6.